Unmasking the triad: a case of severe iron deficiency anemia revealing underlying autoimmune hypothyroidism and celiac disease - Baqai, Haider Z.; Hamza, Muhammad; Asjad, Wafa; Nawaz, Raja N.; Amir, Imaad U. (International Journal Of Community Medicine And Public Health, 2025)
Anemia is the most common hematologic disorder worldwide, iron deficiency being the leading one. Often, anemia is the presenting sign of a more serious underlying condition, which is left untreated and can generate consequent morbidity. Heavy menstrual bleeding (HMB) plays a major role in iron deficiency, especially in women of reproductive age. In this report, we presented an interesting case of a 43-year-old female who presented to the gynecology department of a tertiary care hospital in Islamabad with symptoms of easy fatigability, generalized body weakness, and HMB for the past 3 months. She was admitted to the gynecology ward because of severe iron deficiency anemia. Haemoglobin (Hb) 6.1 g/dl with low mean corpuscular volume (MCV), low serum iron and ferritin levels, and high total iron-binding capacity (TIBC). She was treated with IV iron therapy for iron deficiency and tranexamic acid to stop bleeding. Due to the absence of an obvious gynecological cause, she was referred to the medical outpatient department (OPD) for further evaluation. Further investigations revealed markedly reduced T4 levels and positive anti-thyroid antibodies, dyslipidemia, and grade 2 fatty liver disease. She was initiated on levothyroxine, statins, and proton pump inhibitors (PPIs). Despite Hb improvement, she complained about persistent body aches, muscle pain, and backache. On additional workup, serum calcium and vitamin D levels were low, and anti-tissue transglutaminase IgA and IgG tests appeared positive. She was started on a lifelong gluten-free diet with calcium and vitamin D supplementation. Follow-up and monitoring for osteoporosis and nutritional deficiencies were done.